EFEK HIDROTERAPI TERHADAP LANSIA DENGAN HIPERTENSI DI KLINIK PRATAMA RAWAT INAP GRAHA AMANAH - Mayasari, Destianti Indah; Pramithasari, Intan Diah; Rahmasari, Intan (Universitas Kadiri, 2024)
Hypertension is still a threat to increase blood pressure, especially in the elderly. Hypertension is